2021
DOI: 10.1108/jsm-12-2020-0506
|View full text |Cite
|
Sign up to set email alerts
|

“Is it all just lip service?”: on Instagram and the normalisation of the cosmetic servicescape

Abstract: Purpose To better understand the uptake of cosmetic procedures in the wake of Instagram, this study aims to unravel how the aesthetic labour of influencers acts as the packaging of the cosmetic servicescape. In doing so, the authors contribute to theorising of aesthetic and emotional labour within the services marketing literature, fleshing out the bodywork of influential others not as employees but endorsers, who act like the “walking billboards” (Zeithaml and Bitner, 2003) for the cosmetic service industry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 57 publications
(179 reference statements)
0
9
0
Order By: Relevance
“…Effectively, social media using ARF have been accused by an increasing number of studies to promote "Snapchat dysmorphia" [9], a particular occurrence of body dysmorphic disorders (BDD), consisting in a misalignment between the desired image of one's body and the one actually perceived, due to continuous and intensive use of beautification ARF [10,11]. In turn, Snapchat dysmorphia would lead to lower levels of self-esteem [12] and higher levels of depression [13][14][15]; to several disorders of nutritional behaviour [16] and more frequent use of plastic surgery [17][18][19]; to selfobjectification [20,21] and adaptation to stereotypical socio-cultural aesthetic standards [22] (including racial and skin-colours ones [23]); to "aesthetic labour" [24] and mutual surveillance through female "policing gazes" [25]. However, other studies have shown that beautification is neither the only reason for the use of ARFs nor the prevailing one; in fact, aesthetic motivations are flanked by entertainment, coolness, curiosity, social interaction, silliness, having fun, creativity, brand "fandomship" and so on [26][27][28][29].…”
Section: Arf As Assemblagesmentioning
confidence: 99%
“…Effectively, social media using ARF have been accused by an increasing number of studies to promote "Snapchat dysmorphia" [9], a particular occurrence of body dysmorphic disorders (BDD), consisting in a misalignment between the desired image of one's body and the one actually perceived, due to continuous and intensive use of beautification ARF [10,11]. In turn, Snapchat dysmorphia would lead to lower levels of self-esteem [12] and higher levels of depression [13][14][15]; to several disorders of nutritional behaviour [16] and more frequent use of plastic surgery [17][18][19]; to selfobjectification [20,21] and adaptation to stereotypical socio-cultural aesthetic standards [22] (including racial and skin-colours ones [23]); to "aesthetic labour" [24] and mutual surveillance through female "policing gazes" [25]. However, other studies have shown that beautification is neither the only reason for the use of ARFs nor the prevailing one; in fact, aesthetic motivations are flanked by entertainment, coolness, curiosity, social interaction, silliness, having fun, creativity, brand "fandomship" and so on [26][27][28][29].…”
Section: Arf As Assemblagesmentioning
confidence: 99%
“…Instagram has become a popular platform for influencer marketing, it is the second most popular social media platform globally (behind WhatsApp) with 715 million users (W.A.S., 2022), offering a large potential audience that can be easily reached via organic ads or influencers. For this, Instagram is considered the retail arm of social media dissemination and revolutionizes organizational communication mainly through digital influencers (Rodner, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Such dimensions were selected because they have an impact on online communications, underscoring the need to take cultural differences into account in custom social media strategies (Tsai and Men, 2017). And Instagram was chosen as it is considered the retail arm of social media dissemination and revolutionizes organizational communication mainly through digital influencers (Rodner, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…By self-discrepancy theory, an individual may develop dissatisfaction with their body if their actual body does not align with their ideal body [9]. Therefore, where an individual receives negative responses through signaling by others about their images on social media platforms, it is likely that they will develop a body dysmorphic disorder.…”
Section: How Do Social Media Constitute Body Dysmorphic Disordermentioning
confidence: 99%